Genomic landscape of pediatric B-other acute lymphoblastic leukemia in a consecutive European cohort - Zaliova, Marketa; Stuchly, Jan; Winkowska, Lucie; Musilova, Alena; Fiser, Karel; Slamova, Martina; Starkova, Julia; Vaskova, Martina; Hrusak, Ondrej; Sramkova, Lucie; Stary, Jan; Zuna, Jan; et al. (Haematologica, 2019)
Novel biological subtypes and clinically important genetic aberrations (druggable lesions, prognostic factors) have been described in B-other acute lymphoblastic leukemia (ALL) during the last decade; however, due to a lack of studies on unselected cohorts, their population frequency and mutual associations still have to be established. We studied 110 consecutively diagnosed and uniformly treated childhood B-other patients using single nucleotide polymorphism arrays and whole exome/transcriptome sequencing. The frequency of DUX4-rearranged, BCR-ABL1-like, ZNF384-rearranged, ETV6-RUNX1-like, iAMP21 and MEF2D-rearranged subtypes was 27%, 15%, 5%, 5%, 4%, and 2%, respectively; 43% of cases were not classified into any of these subtypes (B-rest). We found worse early response to treatment in DUX4-rearranged leukemia and a strong association of ZNF384-rearranged leukemia with B-myeloid immunophenotype. Of the druggable lesions, JAK/STAT-class and RAS/RAF/MAPK-class aberrations were found in 21% and 43% of patients, respectively; an ABL-class aberration was found in one patient. A recently described negative prognostic factor, IKZF1plus , was found in 14% of patients and was enriched in (but not exclusive for) BCR-ABL1-like subtype. PAX5 fusions (including 4 novel), intragenic amplifications and P80R mutations were mutually exclusive and only occurred in the B-rest subset, altogether accounting for 20% of the B-other group. PAX5 P80R was associated with a specific gene expression signature, potentially defining a novel leukemia subtype. Our study shows unbiased European population-based frequencies of novel ALL subtypes, recurrent (cyto)genetic aberrations and their mutual associations. This study also strengthens and widens the current knowledge of B-other ALL and provides an objective basis for optimization of current genetic diagnostics.
Keywords: mutace; regulace genové exprese u nádorů; Female; Europe; Infant; dítě; předškolní dítě; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; ženské pohlaví; Gene Expression Regulation, Neoplastic; fúzní onkogenní proteiny; Adolescent; Genomics; lidé; Evropa; Mutation; Oncogene Proteins, Fusion; následné studie; prognóza; kohortové studie; Cohort Studies; Follow-Up Studies; Male; nádorové biomarkery; chromozomální aberace; kojenec; Child, Preschool; Prognosis; Biomarkers, Tumor; transkriptom; Child; mužské pohlaví; pre-B-buněčná leukemie; Transcriptome; mladiství; Chromosome Aberrations; genomika; Humans